Corporate Social Responsibility Program in Ecotourism Development of Mempawah Mangrove Park - gumilang, agum; Dolorosa, Eva; Kurniati, Dewi (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 2 (2021): Vol.15, No.2, 2021DO - 10.24843/SOCA.2021.v15.i02.p02, 2021)
Mangrove ecotourism has various functions and benefits. It also plays an important role in human life environmentally, socially, culturally, and economically. In maintaining the coastal ecosystem of mangrove forests through the development of Mempawah Mangrove Park ecotourism, Mempawah Regency is inseparable from the involvement of Corporate Social Responsibility Program carried out by several companies. This research aimed to formulate priority criteria and optimal alternatives for the Corporate Social Responsibility Program in developing Mempawah Mangrove Park ecotourism in Mempawah Regency. 38 respondents were taken by purposive sampling. This study used qualitative descriptive analysis, namely Analysis Hierarchy Process (AHP) using Expert Choice 11 Software. The results showed that the main priority of the Corporate Social Responsibility program in developing Mempawah Mangrove Park ecotourism was the social and cultural aspects. The second priority is environmental aspect, the third is education aspect, and the last is economic aspect. The top alternative priority in corporate social responsibility program in the development of Mempawah Mangrove Park ecotourism is to attract visitors. The second alternative priority is the mangrove ecotourism conservation program, the third is the knowledge transfer about mangroves to visitors and the community around Mempawah Mangrove Park ecotourism, and the last is for community welfare.